Respuesta :
Third option.
Use y = mx + b (slope-intercept form) to get
y = (1/3)x + b.
Then plug in the point (1,-2) for x and y to figure out b...
-2 = (1/3)(1) + b
-2 - 1/3 = b, so b = -7/3
Now you have y = (1/3)x - 7/3. Convert to standard form by multiplying each term by 3 to get
3y = x - 7. Then move the 3y to the other side to get 0 = x - 3y - 7
Use y = mx + b (slope-intercept form) to get
y = (1/3)x + b.
Then plug in the point (1,-2) for x and y to figure out b...
-2 = (1/3)(1) + b
-2 - 1/3 = b, so b = -7/3
Now you have y = (1/3)x - 7/3. Convert to standard form by multiplying each term by 3 to get
3y = x - 7. Then move the 3y to the other side to get 0 = x - 3y - 7
Answer: [tex]x-3y+7=0[/tex]
Step-by-step explanation:
The equation of line passing from point (a,b) and has slope m is given by :-
[tex](y-b)=m(x-a)[/tex]
Given : Point = (1,-2)
Slope of line= [tex]\dfrac{1}{3}[/tex]
Now, the equation of a line that passes through point (1,-2) and had a slope of [tex]\dfrac{1}{3}[/tex] will be :-
[tex](y-(-2))=\dfrac{1}{3}(x-1)\\\\\Rightarrow\ 3(y+2)=x-1\\\\\Rightarrow\ 3y+6=x-1\\\\\Rightarrow\ x-3y+7=0[/tex]
Hence, the equation of a line, in general form that passes through point (1,-2) and had a slope of [tex]\dfrac{1}{3}[/tex] is [tex]x-3y+7=0[/tex]